Improving the Resilience of Livelihoods to Natural Disasters - Poundrik, Sandeep (World Bank, Washington, DC, 2012)
Earthquakes, floods, cyclones, and such other hazards each year affect approximately 200 million people. Developing countries absorbed 98 percent of these disasters and accounted for nine out of ten disaster-related deaths in the period 1991-2005. In fact, low and middle income countries suffer more severe and widespread degradation than do wealthy countries, whose insurance market covers highly valued property and where sophisticated tools report absolute economic loss. To make the obvious apparent, the US$40 million losses caused by Hurricane Andrew in the United States represented 0.3 percent of gross development product (GDP), while one tsunami in the Maldives decimated 66 percent of GDP. Natural disasters, in terms of sheer loss, disproportionately impact low and middle income countries.